CRIMINAL LIABILITY OF PIMPS IN HUMAN TRAFFICKING: A Case Study of 32/Pid.Sus/2024/PN Tkn - Wahyuni, Rezeki Ananda Putri; Surya, Achmad (FOCUS: Jurnal of Law, 2025)
The aim of this research is to explore the factors influencing the Takengon District Court Judge's decision in case Number 32/Pid.Sus/2024/PN Tkn and to evaluate the criminal accountability associated with prostitution pimping (Case Study Number: 32/Pid.Sus/2024/PN Tkn). This research employs a normative, juridical, and prescriptive methodology, utilizing both the statute and case approaches. The findings indicated that the judge's rationale for the ruling in Number 32/Pid.Sus/2024/PN Tkn highlighted aggravating factors, specifically the defendant's actions disrupting the community and the harm caused to Aceh's reputation as the Mecca Porch, along with mitigating circumstances regarding the defendant. From a legal standpoint, this case should involve three parties subject to penalties in keeping with Article 23, paragraph (1) of Qanun Aceh Number 6 of 2021 related to Jinayat Law, since Aceh has specific Islamic laws that categorically forbid prostitution.